Dielectric Monitoring the Effect Green Copper Oxide Nanoparticles Incubation with Baker's Yeast Cells Suspension (Journal of Nuclear Technology in Applied Science, 2020)
The current era of emerging nano-technology has immersed us in a sea of nanomaterials used in different fields of life. Copper oxide nanoparticles (CuONPs) are used in many industrial and medical issues. many previous studies were conducted upon CuONPs cytotoxicity interaction upon the biological cells. The current monitoring interventions of cell viability was carried out by several methods mainly depends on cytolysis or membrane leakage. unfortunately many of these assays are invasive to cell and the others are toxic. on the other-side physical means interventions play a crucial role. Among Electrical impedance measurement was a rational tool to investigate the biological materials by the mean of two electrodes in a sophisticated designed measuring cell. The current attempt aims at dielectric monitoring in form permittivity and conductivity spectrum of green (CuONPs) incubation effect with baker's yeast cells suspension. CuONPs are characterized by electron microscopy and Fourier transformer infred(FTIR) was investigated under room condition.
Keywords: dielectrics; green synthesis; copper oxide; nanoparticles; yeast